2014
DOI: 10.1093/nar/gkt1356
|View full text |Cite
|
Sign up to set email alerts
|

A novel intermediate in transcription initiation by human mitochondrial RNA polymerase

Abstract: The mitochondrial genome is transcribed by a single-subunit T7 phage-like RNA polymerase (mtRNAP), structurally unrelated to cellular RNAPs. In higher eukaryotes, mtRNAP requires two transcription factors for efficient initiation—TFAM, a major nucleoid protein, and TFB2M, a transient component of mtRNAP catalytic site. The mechanisms behind assembly of the mitochondrial transcription machinery and its regulation are poorly understood. We isolated and identified a previously unknown human mitochondrial transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 49 publications
(78 reference statements)
4
90
0
Order By: Relevance
“…In addition to its function in mtDNA compaction, TFAM is also an essential component of the mammalian mtDNA transcription initiation complex (13). It specifically binds the mitochondrial promoters to recruit the mitochondrial RNA polymerase (POLRMT), which, in turn, recruits mitochondrial transcription factor B2 (14,15). Crystallographic studies have revealed that TFAM induces a 180°U-turn when bound to promoters or unspecific mtDNA sequences (16)(17)(18).…”
mentioning
confidence: 99%
“…In addition to its function in mtDNA compaction, TFAM is also an essential component of the mammalian mtDNA transcription initiation complex (13). It specifically binds the mitochondrial promoters to recruit the mitochondrial RNA polymerase (POLRMT), which, in turn, recruits mitochondrial transcription factor B2 (14,15). Crystallographic studies have revealed that TFAM induces a 180°U-turn when bound to promoters or unspecific mtDNA sequences (16)(17)(18).…”
mentioning
confidence: 99%
“…resembling the promoter-binding domain of the T7 RNA polymerase, and an N-terminal extension (NTE) that includes a domain containing PPR (pentatricopeptide) motifs [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal domain is more divergent, but a structural similarity among orthologous mtRNAP sequences and the phage protein is still apparent [29]. In the human protein this region has been implicated in transcription initiation through interactions with the promoter and the two transcription factors [28]. In the yeast Rpo41 protein this region also appears to be involved in promoter recognition and in interactions with the sole transcription factor (Mtf1p) [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, increased TFAM expression reduced neuronal pathologies and increased patient survival rate, deeming it clinically beneficial (Correia et al 2011). A significant component of mitochondrial transcription, the mitochondrial RNA polymerase, requires TFAM and TFBM2 for efficient initiation (Morozov et al 2014;St John et al 2006).…”
Section: Tfam Roles and Functionmentioning
confidence: 99%
“…TFBM2 can reposition the specificity loop of mtRNAP to recognize specific promoters (Morozov et al 2014;Morozov et al 2015). Mitochondrial protein formation is regulated by mitochondrial ribosomes, consisting of two subunits: the small (28S) mitochondrial ribosome subunit and the larger (55S) subunit.…”
Section: Tfam Roles and Functionmentioning
confidence: 99%